2021
DOI: 10.21091/mppa.2021.4030
|View full text |Cite
|
Sign up to set email alerts
|

Novel Ultrasonographic Thickness and Strength Assessments of the Flexor Digitorum: A Reliability Analysis

Abstract: OBJECTIVES: Clinical conditions such as focal dystonia often require the assessment of atrophy and weakness of the finger muscles. However, due to a lack of well-established protocols, the current investigation focused on assessing the reliability of thickness and strength assessments of the flexor digitorum (FD) muscle, including both the superficialis and profundus components. As a secondary assessment, the reliability of the strength measurement of the extensor digitorum muscle was examined as well. METHOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…However, results deriving from the strength assessment of the extensor digitorum should be interpreted with caution. Besides its excellent intraclass correlation coefficient (>0.92), reported by Ioannou et al [24], strength assessments of the extensor digitorum showed a larger detectable change (≤12%) as compared to the detectable change of the thickness and strength of the flexor digitorum (≤5.1%). This may also explain the larger variability of data in this particular assessment (see Figure 1).…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…However, results deriving from the strength assessment of the extensor digitorum should be interpreted with caution. Besides its excellent intraclass correlation coefficient (>0.92), reported by Ioannou et al [24], strength assessments of the extensor digitorum showed a larger detectable change (≤12%) as compared to the detectable change of the thickness and strength of the flexor digitorum (≤5.1%). This may also explain the larger variability of data in this particular assessment (see Figure 1).…”
Section: Discussionmentioning
confidence: 50%
“…That strength can be gained without a major increase in muscle size was shown using MRI cross-section images of healthy participants before and after a strength training protocol [35,36]. A possible explanation could be an adaptation of the nervous system that allows greater force generation without any morphological changes in the muscle itself [24,37,38].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current assessment approach focuses on assessing the thickness and activity of the flexor digitorum muscle, which includes both the superficialis and profundus components. It is also necessary to examine the strength of the extensor digitorum muscle as a second assessment standard [28]. This illustrates that the main muscles that generate force when a person clenches a fist are flexor digitorum muscle and extensor digitorum muscle.…”
Section: Application and Preliminary Resultsmentioning
confidence: 99%